Social services made simple - Byrne, Tony, 1937- (Made simple books., 1990)
Social Services provides an introduction to the social services in Great Britain. This fourth edition aims to take account of a number of important changes in British social services since 1984 and to generally up-date the whole text. This volume was substantially completed towards the end of 1988, and updated until the summer/autumn 1989.